2018
DOI: 10.1080/17549507.2018.1441439
|View full text |Cite
|
Sign up to set email alerts
|

How important is embeddedness in predicting Australian speech–language pathologists’ intentions to leave their jobs and the profession?

Abstract: The findings indicate that the proposed parsimonious model adequately captures predictors of speech-language pathologists' turnover and occupation attrition intentions. Workplaces and the profession may wish to consider these retention factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Time restrictions, a lack of appropriate and adequate support, insufficient assets to complete a project, ineffective coworkers, career issues, and other reasons can all add to stress. [4] The result of a large workload is lower performance, which leads to low morale and significant employee turnover. Many studies have looked into how men and women deal with stress as a result of various workplace pressures in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Time restrictions, a lack of appropriate and adequate support, insufficient assets to complete a project, ineffective coworkers, career issues, and other reasons can all add to stress. [4] The result of a large workload is lower performance, which leads to low morale and significant employee turnover. Many studies have looked into how men and women deal with stress as a result of various workplace pressures in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Only one (Warden et al, 2008) stated the methodological orientation that underpinned the study. The two mixed methods papers that gathered qualitative data through large-scale surveys (Heritage, Quail & Cocks, 2018;Loan-Clarke, et al, 2009) did not lend themselves well to the COREQ criteria, with some items being irrelevant. Of the fourteen criteria that were relevant to both, nine were met in each case.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…They also reported that 6.8% (n=162) of their participants described specific stressful events as a reason to "seriously think about leaving" the NHS, 20.2% (n=109) left the NHS due to stress, and 13.3% felt that stress reduction was an action that could be taken by NHS management to increase the chance that they would remain in or return to the NHS. Heritage et al (2018) reported that a lack of job satisfaction contributed significantly to the intention to leave the profession. In addition, their qualitative content analysis identified elements of job satisfaction which encouraged participants to stay in their current position (e.g.…”
Section: The Effect Of Slp Job Satisfaction Stress/stressors and Burnout On Recruitment And Retentionmentioning
confidence: 99%
“…If untreated, BS can lead to reduced productivity, absenteeism, tense occupational relationships, high turnover rates and a low quality of service. 19 , 20 The latter is especially problematic for patients, especially those with dysphagia who require immediate treatment by speech pathologists. 20 …”
Section: Introductionmentioning
confidence: 99%
“…The way these professionals perceive their work, the challenges they face, their dissatisfaction with their jobs and the intention to leave their profession are all major concerns which must be further investigated and better understood. 20 …”
Section: Introductionmentioning
confidence: 99%